2021
DOI: 10.1007/s10901-020-09802-z
|View full text |Cite
|
Sign up to set email alerts
|

Slums, women and sanitary living in South-South Nigeria

Abstract: How much do slums affect women's ability to negotiate access to water, sanitation and hygiene (WaSH)? We used random narratives, interviews, and a review of literature from theoretical and secondary sources to capture the experiences of slum dwellers in South-South Nigeria. Our findings demonstrate that women and girls bear disproportionate burden and risk of poor and inadequate WaSH services in the course of domestic supplies and management and making tough choices in negotiating between personal sanitary nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…A recent study conducted in south-west Nigeria reported a smaller proportion (48%) of drinking water with low fluoride from similar sources: ground water-well or borehole [71,72]. Access to clean drinking water is generally a challenge for a large proportion of the Nigerian population but the situation is worse in the slums [73,74]. The non-recognition of slums in official discourses often limit their consideration in the planning of essential public services such as water [74].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…A recent study conducted in south-west Nigeria reported a smaller proportion (48%) of drinking water with low fluoride from similar sources: ground water-well or borehole [71,72]. Access to clean drinking water is generally a challenge for a large proportion of the Nigerian population but the situation is worse in the slums [73,74]. The non-recognition of slums in official discourses often limit their consideration in the planning of essential public services such as water [74].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The gender division of roles pushes the duty regarding WASH-related administration onto women and girls [30]. The distance to a water source builds up the time expected for income-producing exercises, family tasks and childcare [5,31].…”
Section: Women and Girls And Their Right To Gender Equality And Water...mentioning
confidence: 99%
“…The distance to a water source builds up the time expected for income-producing exercises, family tasks and childcare [5,31]. A young girl is given the duty of providing water for the home while the mother centers around the coordination, including the sanitation and hygiene of the home [30]. Presently, as a feature of SDG evaluation, markers are gathered on access to water on the premises (SDG 6) and the extent of time spent on unpaid domestic and care work by sex and age (SDG 5) [29].…”
Section: Women and Girls And Their Right To Gender Equality And Water...mentioning
confidence: 99%
See 1 more Smart Citation
“…The direct connections between the main keywords like the link between "water supply" in green cluster and "sustainable development" in red cluster (link strength is 56) demonstrates the direct link between the role of water supply in attaining SDG 6. Though not one of the topmost keywords, the occurrence of the keywords like "female" in the green cluster as "water supply" (link strength between "female" and "water supply is 11), "water quality" (link strength between "female" and "water supply is 11) and "sanitation" (link strength between "female" and "sanitation" is 13) demonstrates the increasing focus of studies on water supply and sanitation issues from a gender perspective [66][67][68]. On the other hand, relatively lesser focus on "water governance" (total link strength of 184 with 75 links), "ecosystems" (total link strength of 116 with 64 links), "water security" (total link strength of 119 with 74 links) or "rural water supply" (total link strength of 119 with 60 links) reveals the lack of studies or lack of emphasis of studies to link SDG 6 and its targets with water governance, water security or ecosystem-based approaches.…”
Section: Keyword Analysismentioning
confidence: 99%